(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the theoretical and practical foundations for the formation of social-pedagogical competencies of future teachers in higher education institutions. The essence and content of the concept of social-pedagogical competence are explained, and its structural components—communicative, social, reflective, and emotional-intellectual aspects—are scientifically interpreted. Furthermore, the pedagogical conditions and effective methods for developing these competencies in future teachers are identified. In particular, the implementation of a competency-based approach, the use of interactive teaching methods, the strengthening of practical activities, and the development of reflective processes are substantiated as important factors. The results of the study contribute to improving the professional training of future teachers in the system of higher pedagogical education, developing their social-pedagogical potential, and enhancing the quality of education.